2020
DOI: 10.18596/jotcsa.590621
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of anti-bacterial biocomposite nanofibers fabricated by electrospinning method

Abstract: Developing technology and increasing the number of living creatures on Earth increase the demand for biomaterials each passing day. Recently, biocomposites and biodegradable biomaterials have begun to attract attention in many areas of use. Electrospinning technique is preferred as a quite consolidated technique in the production of outstanding polymer and/or nanofiber matrixes. However, obtained biocomposite nanofibers can cause microbiological infections during or after their usage. Therefore, it is very imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…Figure 6 depicts the plot of the particle fraction as a function of the particle size distribution, and it appears that the average size distribution is between 0.4 and 8 μm. This is consistent with the data provided by Kesmez et al [ 40 ], who indicated the formation of wide agglomerated particles having an average particle size ranging from 1 to 15 μm.…”
Section: Resultssupporting
confidence: 93%
“…Figure 6 depicts the plot of the particle fraction as a function of the particle size distribution, and it appears that the average size distribution is between 0.4 and 8 μm. This is consistent with the data provided by Kesmez et al [ 40 ], who indicated the formation of wide agglomerated particles having an average particle size ranging from 1 to 15 μm.…”
Section: Resultssupporting
confidence: 93%
“…The WS 2 QDs show the absorption bands at 671 and 928 cm –1 , which appeared due to W–S and S–S bonds, confirming the formation of WS 2 and the peaks that appeared at 1461 and 1645 cm –1 are due to the stretching deformation of the hydroxyl group. The peaks observed at 2922 and 3449 cm –1 were associated with the atmospheric −OH stretching. , …”
Section: Resultsmentioning
confidence: 97%
“…The peaks observed at 2922 and 3449 cm −1 were associated with the atmospheric −OH stretching. 37,38 The relative amounts of the β phase in pristine and WS 2reinforced PVDF-HFP were analyzed using the relative absorption intensities of β and α phase and the method proposed by Gregorio & Cestari…”
Section: Resultsmentioning
confidence: 99%
“…2− [36], while the one at 870 cm −1 is associated with the υ 2 symmetric stretching vibrations of carbonate ions, which can be incorporated into the apatites from atmospheric CO 2 [32]. The peak at 3338 cm −1 corresponds to the ion stretching of the OH − , confirming the presence of the hydroxyl group, while the water that is associated with hydroxyapatite can be seen at 3471 and 1641 cm −1 , respectively, corresponding to the stretching and bending vibrations [37][38][39]. These FT-IR ATR analyses could have detected vestigial organic fractions in the samples, such as collagen.…”
Section: Ftir Atr Spectroscopymentioning
confidence: 99%